Geopolymerization of Plastic Waste for Sustainable Construction: Unveiling Novel Opportunities in Building Materials - Haq, Md. Zia ul; Sharma, Vishal; Sood, Hemant; Kumar, Rajesh; Joshi, Kapil; Manisha, Kumari; Lakhanpal, Sorabh; Chary, M. Rathna; Kumar, Kaushal (E3S web of conferences, 2023)
This study provides an in-depth bibliometric analysis of the research land-scape of Geopolymer concrete using data from two of the leading scientific databases, Scopus and Web of Science. The analysis covers a time span of 2010 to 2022 and provides a comprehensive evaluation of the growth, age, impact, and collaboration of research in the field. The results show that the annual growth rate of research in Geopolymer concrete is substantial, with a 43.92% increase in the number of documents in Scopus and 15.76% in Web of Science. Furthermore, the document average age is relatively low, with 1.59 years in Scopus and 3.11 years in Web of Science, suggesting that the research in this field is recent and dynamic. The study also found that the research in Geopolymer concrete is highly cited, with an average of 11.69 ci-tations per document in Scopus and 18.69 in Web of Science.The authorship and document type analysis provides valuable insights into the research col-laboration and output in the field. The results show a high level of collabora-tion, with an average of 4.29 co-authors per document in Scopus and 3.47 in Web of Science. Additionally, the majority of the documents in the field are articles, with a smaller number of conference papers, book chapters, and re-views. In conclusion, this study provides a comprehensive overview of the research landscape of Geopolymer concrete and highlights the areas of strength and potential for future research. The results of the analysis can be useful for researchers, policymakers, and stakeholders in the field of Geopol-ymer concrete to understand the current state of the research, identify poten-tial gaps and opportunities, and plan future research activities.Page layout